2023
DOI: 10.1096/fj.202300420r
|View full text |Cite
|
Sign up to set email alerts
|

Irisin ameliorates diabetic kidney disease by restoring autophagy in podocytes

Weiyan Lai,
Dan Luo,
Yin Li
et al.

Abstract: Many studies have highlighted the importance of moderate exercise. While it can attenuate diabetic kidney disease, its mechanism has remained unclear. The level of myokine irisin in plasma increases during exercise. We found that irisin was decreased in diabetic patients and was closely related to renal function, proteinuria, and podocyte autophagy injury. Muscle‐specific overexpression of PGC‐1α (mPGC‐1α) in a mouse model is known to increase plasma irisin levels. The mPGC‐1α mice were crossed with db/m mice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 48 publications
(103 reference statements)
0
3
0
Order By: Relevance
“…However, the mechanism through which exercise-induced irisin activates AMPK in the kidneys remains unclear, and it is speculated that irisin may bind to the αV-integrin receptor on the kidney cells, causing renal AMPK activation somehow. In addition, the study of Lai et al [121] showed that increased irisin in plasma can inhibit the overactivation of the high-glucose-induced PI3K/AKT/mTOR signaling pathway in human podocytes, thereby restoring podocyte autophagy. Therefore, exercise may ameliorate kidney injury by activating the AMPK signaling pathway or inhibiting theAKT signaling pathway through irisin secreted by the skeletal muscles during exercise, which needs to be further investigated (Figure 7).…”
Section: Irisinmentioning
confidence: 99%
“…However, the mechanism through which exercise-induced irisin activates AMPK in the kidneys remains unclear, and it is speculated that irisin may bind to the αV-integrin receptor on the kidney cells, causing renal AMPK activation somehow. In addition, the study of Lai et al [121] showed that increased irisin in plasma can inhibit the overactivation of the high-glucose-induced PI3K/AKT/mTOR signaling pathway in human podocytes, thereby restoring podocyte autophagy. Therefore, exercise may ameliorate kidney injury by activating the AMPK signaling pathway or inhibiting theAKT signaling pathway through irisin secreted by the skeletal muscles during exercise, which needs to be further investigated (Figure 7).…”
Section: Irisinmentioning
confidence: 99%
“…By targeting Bcl-2 with baicalin, apoptosis can be reduced or become a new target [ 62 ]. The activation of PI3K/AKT/mTOR, a recognized autophagy inhibitory pathway, decreases cellular autophagy [ 63 ]. However, podocytes rarely use mTOR for regulation, so new findings have shown that osmotic ion channels (TRPC6) can damage autophagy by activating calpain, as determined in a new study on the relationship between podocyte cytoskeleton and autophagy [ 64 ].…”
Section: Diabetic Nephropathy and Mitochondrial Dysfunctionmentioning
confidence: 99%
“…Recent research indicates that the phosphatidylinositol-3-kinase/protein kinase B/mammalian target of rapamycin (PI3K/Akt/mTOR) signaling pathway plays a crucial role in podocytes, primarily by downregulating autophagy ( Yang X et al, 2020 ; Lai et al, 2023 ). Following DN, elevated levels of inflammatory factors and reactive oxygen species (ROS) can activate cell surface receptors, initiating the PI3K activation process.…”
Section: Roles Of Alpinia Oxyphylla On Dnmentioning
confidence: 99%